2014
DOI: 10.1002/2013jb010545
|View full text |Cite
|
Sign up to set email alerts
|

Controls on segmentation and morphology along the back‐arc Eastern Lau Spreading Center and Valu Fa Ridge

Abstract: Back-arc spreading centers increasingly depart from mid-ocean ridge (MOR) characteristics with proximity to the arc volcanic front. The close association of these departures with slab-derived materials in erupted lavas suggests that subduction-related chemical effects are their primary cause. The Eastern Lau Spreading Center (ELSC) and Valu Fa Ridge (VFR) are type examples of this process. Together they constitute a first-order spreading center in the Lau back-arc basin that progressively converges on the Tofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 60 publications
(165 reference statements)
6
34
0
Order By: Relevance
“…This does not appear to be along-axis mixing from the wetter ELSC2; seismic imaging of the crustal magmatic system at this OSC (20 • 10 S) shows that the low velocity regions associated with the two ridge limbs are discontinuous down to at least ∼5 km depth, indicating the crustal magmatic system and the bulk of the associated thermal anomalies are distinct throughout the mid-toupper crust (Dunn et al, 2013). Further south in Domain II, Sleeper and Martinez (2014) also noted a correlation between OSCs and geochemical tracers of subduction input, and suggested that the OSCs lie along slab trajectories from arc volcanoes and represent "hot fingers" of more hydrous melting in the mantle wedge (e.g., Tamura et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This does not appear to be along-axis mixing from the wetter ELSC2; seismic imaging of the crustal magmatic system at this OSC (20 • 10 S) shows that the low velocity regions associated with the two ridge limbs are discontinuous down to at least ∼5 km depth, indicating the crustal magmatic system and the bulk of the associated thermal anomalies are distinct throughout the mid-toupper crust (Dunn et al, 2013). Further south in Domain II, Sleeper and Martinez (2014) also noted a correlation between OSCs and geochemical tracers of subduction input, and suggested that the OSCs lie along slab trajectories from arc volcanoes and represent "hot fingers" of more hydrous melting in the mantle wedge (e.g., Tamura et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…Unlike some back-arc extensional settings where broad crustal rifting and subsequent partial melting and modification of pre-existing arc crust has been proposed (e.g., Takahashi et al, 2008), most new crustal formation in the eastern Lau basin occurs primarily at wellorganized spreading centers. Seismic imaging along these spreading centers indicates a single narrow axial magmatic system (e.g., Jacobs et al, 2007;Dunn et al, 2013), and sonar and magnetic data indicate a narrow and persistent axis of crustal formation for >2 Myr (e.g., Sleeper, 2011;Austin, 2012;Sleeper and Martinez, 2014). The current spreading configuration initiated in the north and propagated southward along the Central Lau Spreading Center (CLSC), Eastern Lau Spreading Center (ELSC), and Valu Fa Ridge (VFR), resulting in the basin's current wedge shape (Fig.…”
Section: Settingmentioning
confidence: 99%
“…Differences in melt supply along spreading centers are generally expected to influence axial stresses and lithospheric faulting (e.g., Thatcher and Hill, 1995). In support of that concept, the southward increase in melt supply correlates with a decrease in the spacing and throws of faults (Sleeper and Martinez, 2014), and the implication is that spreading is more magmatically accommodated in the south. The change in melt supply is not gradual, but instead occurs in abrupt transitions.…”
Section: Study Areamentioning
confidence: 93%
“…Activesource seismic studies are not usually designed with the intent to measure three-dimensional variations in anisotropy, but the results thus far are encouraging. Several studies have examined one-dimensional depth-dependent anisotropy in oceanic crust, including measurements along mid-ocean ridge crests (Caress et al, 1992;MacDonald et al, 1994;Sohn et al, 1997;Barclay et al, 1998;Dunn and Toomey, 2001;Barclay and Wilcock, 2004;Tong et al, 2004;Seher et al, 2010), in older oceanic crust (>1 Ma) (Stephen, 1981(Stephen, , 1985White and Whitmarsh, 1984;Shearer and Orcutt, 1986;Detrick et al, 1998), and in back-arc basins (Hirata et al, 1992). Few prior studies have attempted to extract lateral variations in crustal anisotropy at a spreading center (e.g., Sohn et al, 1997;Dunn and Toomey, 2001;Weekly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of roughness damping and perturbation-amplitude damping are applied to ensure model smoothness and reduce spurious anomalies in regions with low ray coverage, following Barmin et al (2001). Spatially variable weak azimuthal anisotropy with a 2θ velocity variation (Smith and Dahlen, 1973) for Rayleigh waves is included in the inversion.…”
Section: Phase Velocity Map Inversionmentioning
confidence: 99%